Preservation of Cyanobacterial UVR‐Shielding Pigment Scytonemin in Carbonate Ooids Formed in Pleistocene Salt Lakes in the Qaidam Basin, Tibetan Plateau. Issue 17 (5th September 2019) - Sun, Yu; Li, Yiliang; Li, Long; He, Hongping
Abstract: The formation of ooids and their use as a proxy to trace biogeochemical cycles have long been controversial. Here, we examined three beds of evaporite‐cemented ooids in the Qaidam Basin, including a layer of dolomitic ooids formed at 293 ± 4 kyr and cemented by gypsum at 266 ± 3 kyr, a layer of aragonitic ooids formed at 163 ± 1 kyr and cemented by halite at 111 ± 0.8 kyr, and another layer of aragonitic ooids formed at 38 ± 0.5 kyr and cemented by gypsum at 23 ± 0.3 kyr. The Raman spectra of organic extracts from these ooids indicate ubiquitous preservation of scytonemin, a unique cyanobacterial ultraviolet radiation (UVR)‐shielding pigment. This discovery suggests that ooids are capable of preserving biomarker from their depositional environment. Consequently, ooid may be used as a proxy for tracing biogeochemical processes and potentially applied to the search for life on Mars. Plain Language Summary: Following the later rise of the Tibetan Plateau, the Qaidam Basin to its north has developed an extremely dry climate and consequently a vast area of playas derived from salt lake deposits since the Pleistocene. From this sedimentary system similar to some observed on Mars, we discovered several outcrops of ooids cemented by evaporites in Pleistocene ages. All of these ooids preserve an ultraviolet radiation‐screening pigment, scytonemin, which can only be derived from indigenous photosynthetic cyanobacteria. The ability to preserve organic compounds from their depositional environments suggests that ooids may be a good proxy for tracing microbial activities in ancient salt lakes and potentially be a novel tool for seeking biosignatures on Mars. Key Points: Three carbonate ooids cemented by evaporites from playas in the Qaidam Basin were dated to be 38, 163, and 293 kyr Cyanobacterial ultraviolet radiation‐shielding pigment scytonemin was detected in all ooid samples Ooids may provide a novel proxy to examine extremophiles in closed basins and help the search for life on Mars